Perbandingan Pemeriksaan Tinja Metode Sedimentasi Formol-ether dengan Metode Kato-Katz dalam Mendeteksi Soil-transmitted Helminth.: . - Rilianda Abelira; Hanna Mutiara (Medula, 2023)
Soil-transmitted Helminth (STH) is the most common intestinal parasitic infection that contribute to the global disease burden. Various health problems may occur due to this infection. STH infections can be diagnosed by microscopic examination of the stool. WHO recommends the Kato-Katz method as the gold standard for detecting STH, but this method is less sensitive to mild infections. Another method recommended for mild infections is the formol-ether concentration (FEC) method. Some studies show different results for the comparison of these two methods. This study aims to compare the result of the stool examination between FEC method and the Kato-Katz method in detecting STH. Evaluation of examination methods is important in the search for accurate diagnostic techniques.This study used stored stool samples. The study design was descriptive analytic with cross sectional approach. The sampling technique used is consecutive random sampling. Data were analyse based on STH frequency with McNemar's comparative statistical test. The microscopic picture of the FEC method is clearer than the microscopic picture of Kato-Katz method. The results of stool examination using the FEC method and the Kato-Katz method obtained positive results of 6 samples (20%) and negative samples of 24 samples (80%), same result for both method. The type of worm eggs found was Ascaris lumbricoides with 6 samples (100%). Hookworms (A.duodenale and N. americanus) found by FEC method was 2 samples (33.3%) of 6 positive samples. McNemar test results obtained p value of 1,000 (> α 0.05).There is no statistically significant difference from the results of the comparison of stool examination with the FEC method and the Kato-Katz method using McNemar test.